IMPACT OF TRIGLYCERIDE GLUCOSE INDEX AND TG/HDL RATIO ON TREATMENT OUTCOMES IN ACUTE ISCHEMIC STROKE - Akpinar, Ahmet; Kalyoncu Aslan, Işıl; Ramazanoğlu, Leyla (MNJ (Malang Neurology Journal), 2026)
Background: Insulin resistance is one of the modifiable risk factors for ischemic stroke. Objective: This study aimed to investigate the relationship between treatment success, complications, and the functional status of the patients at 3 months follow up, Triglyceride/Glucose index and Triglyceride/High Density Lipoprotein values in patients who were received intravenous thrombolytic and/or mechanical thrombectomy treatments. Methods: A total of 432 patients aged over 18 years who were treated for acute ischemic stroke were included in the study. The Triglyceride Glucose index was computed using the formula Ln (Fasting Blood Sugar (mg/dl) x Fasting Triglyceride Level (mg/dl)/2) based on blood samples taken on the first day of hospitalization. Etiological evaluation of stroke was performed according to the TOAST classification. Results: Twenty-four hours following intravenous thrombolysis and/or mechanical thrombectomy, patients exhibiting elevated Triglyceride/Glucose index values demonstrated higher NIHSS scores. Moreover, individuals diagnosed with large vessel occlusions had significantly increased Triglyceride/Glucose index and Triglyceride/High Density Lipoprotein ratio levels compared to those with cardioembolic stroke etiology. On the other hand, no meaningful association was identified between Triglyceride/Glucose index and Triglyceride/High Density Lipoprotein values and the duration of hospitalization or modified rankin score outcomes. Conclusion: In this study, no strong evidence was shown regarding the relationship between Triglyceride/Glucose index and Triglyceride/High Density Lipoprotein values and treatment-related complications and functional status at 3-month follow-up in patients who underwent iv thrombolytic and mechanical thrombectomy treatment due to acute ischemic stroke. Prospective studies with longer follow-up of patients are needed on this subject.